2011
DOI: 10.1063/1.3574924
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio investigation on the magnetic ordering in Gd doped ZnO

Abstract: The current study investigates the magnetic properties of the GdxZn1-xO, with x=0.0625 and 0.0185, doped semiconductor using the full potential (linearized) augmented plane wave plus local orbital method. We show that in contrast to the findings of Shi et al. [J. Appl. Phys. 106, 023910 (2009)], the implementation of the Hubbard U parameter to the Gd f states favors an antiferromagnetic phase in both wurtzite GdO and GdxZn1-xO. Spin polarized calculations on GdxZn1-xO indicate that, even if a ferromagnetic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…In addition, s-f exchange can be stronger than f-f or f-p exchange. 8,27 One of the concerns here is related to the location of the Fermi level (E F ) and 4f levels in the band, which is required to establish such magnetic exchange. Earlier theoretical studies showed that the 4f levels lie inside the conduction band (CB) (spin-down) and valence (spin-up) bands in Gd:ZnO.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…In addition, s-f exchange can be stronger than f-f or f-p exchange. 8,27 One of the concerns here is related to the location of the Fermi level (E F ) and 4f levels in the band, which is required to establish such magnetic exchange. Earlier theoretical studies showed that the 4f levels lie inside the conduction band (CB) (spin-down) and valence (spin-up) bands in Gd:ZnO.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…While the same applies to Gd doping, the observed ferromagnetic coupling depends on the crystal structure and positions of the dopant atoms in the host matrix, as well as the distance between RE dopants. 8 FM is observed experimentally in ZnO thin films 9,10 and ZnO nanostructures doped with RE elements, such as Eu, Nd, and Gd. 11,12 In several experiments on ZnO nanowires doped with Gd, huge magnetic moments (3278l B /Gd) were obtained, which is attributed to the exchange interaction between 4f and 6s electrons.…”
mentioning
confidence: 93%
“…8 To determine the preferred Gd positions, total energy calculations are performed for 12 configurations, divided into 3 groups, encompassing surface, sub-surface, and bulk-like regions, as shown in Fig. 1 (groups 1, 2, and 3 …”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations